CARDIOVASCULAR MORTALITY IN 12 RUSSIAN FEDERATION REGIONS – PARTICIPANTS OF THE “CARDIOVASCULAR DISEASE EPIDEMIOLOGY IN RUSSIAN REGIONS” STUDY - S. A. Shalnova; A. O. Konradi; Yu. A. Karpov; A. V. Kontsevaya; A. D. Deev; A. V. Kapustina; M. B. Khudyakov; E. V. Shlyakhto; S. A. Boytsov (Российский кардиологический журнал)
Similarto most developed countries, cardiovascular disease (CVD)is a leading cause of mortality in Russia. The levels of CVD mortality in working-age Russian men and women are the highest in Europe and characterised by marked fluctuations. Up to 60% of fatal CVD cases could be explained by the population levels of cardiovascular risk factors. Presently, however, no data are available to demonstrate the varied prevalence of these risk factors inRussia. The information on the actual health status and cardiovascularrisk factor levels in the Russian population could be obtained only in epidemiological studies. Therefore, the Russian Ministry of Health and Social Development initiated the study “Cardiovascular Disease Epidemiology in Russian Regions”. This study involves 12 Russian regions which differ by their climatic, geographic, economic, and demographic characteristics. This analysis presents the official levels of CVD mortality in respective Russian regions and the associations between mortality and regional per capita income. A marked inter-regional heterogeneity in fatal CVD levels, as well as a significant regional gradient in CVD mortality by income, demonstrates the urgent need for the wide implementation of risk factor monitoring across the Russian regions.